2016
DOI: 10.1002/chem.201504157
|View full text |Cite
|
Sign up to set email alerts
|

The First Enantioselective Organocatalytic Synthesis of 3‐Spiro‐α‐Alkylidene‐γ‐Butyrolactone Oxindoles

Abstract: A new and flexible methodology catalyzed by bifunctional chiral thioureas has been developed to react β-nitro oxindoles 1 with aldehydes. This approach allowed us to achieve the first enantioselective organocatalytic synthesis of 3-spiro-α-alkylidene-γ-butyrolactone oxindoles 3. We examined the scope of the two starting materials and, varying the structure of the β-nitro oxindole 1, intriguing new products, derived from unexpected transformations, have been stereoselectively obtained. The aim of this study was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(8 citation statements)
references
References 105 publications
0
8
0
Order By: Relevance
“…Very recently, Quintavalla et al . reported an aldol/lactonization/elimination domino sequence catalysed by bifunctional thioureas paving the way for the first enantioselective synthesis of 3‐spiro‐α‐alkylidene‐γ‐butyrolactones oxindoles 59 , products which have two potentially bioactive structural motifs: the spirofused oxindole and the α‐alkylidene‐γ‐butyrolactone moieties (Scheme ) 66…”
Section: Asymmetric Aldol Reaction With Active Methinesmentioning
confidence: 99%
“…Very recently, Quintavalla et al . reported an aldol/lactonization/elimination domino sequence catalysed by bifunctional thioureas paving the way for the first enantioselective synthesis of 3‐spiro‐α‐alkylidene‐γ‐butyrolactones oxindoles 59 , products which have two potentially bioactive structural motifs: the spirofused oxindole and the α‐alkylidene‐γ‐butyrolactone moieties (Scheme ) 66…”
Section: Asymmetric Aldol Reaction With Active Methinesmentioning
confidence: 99%
“…The synthesis of spirocyclicindolines from readily available indolin‐2‐one derivatives features a most straightforward avenue toward the spiroindoline substructures which bearing a quaternary carbon center at the C3 position. To date, various 1,3‐dipolar [3+2]‐cycloaddition reactions of 3‐alkyloxindoles, 3‐alkenyloxindoles, 3‐hydroxyloxindoles, 3‐aminooxindoles, or 3‐spiroepoxyoxindoles were utilized as starting materials to give access to spiro[pyrrolidine‐2,3′‐oxindole]s. In 2016, Enders group developed N ‐heterocyclic carbene (NHC) catalyzed [3+4]‐cycloaddition reactions of isatin‐derived enals to synthesize spirobenzazepinones, spiro‐1,2‐diazepinones and spiro‐1,2‐oxazepinones in good yield . Soon after, Tanaka et al reported organocatalytic enantioselective Michael‐Henry cascade reactions to construct spirooxindole polyheterocycles …”
Section: Methodsmentioning
confidence: 99%
“…In 2014, Liang and Xu developed a novel approach to chiral spirooxindole δ‐lactones through bifunctional thiourea catalyzed [5+1] annulation of oxindoles with ester‐linked bisenones (Scheme a) . An enantioselective synthesis of spirooxindole alkylidene‐γ‐lactones was successfully developed by Quintavalla and co‐workers through organocatalytic aldol reaction of C3‐alkylated oxindoles with aldehydes (Scheme b) . The first asymmetric synthesis of spirooxindole γ‐lactams was accessed by an oxoindolin‐3‐ylidene involving a four‐component reaction promoted by a recyclable fluorous bifunctional cinchona alkaloid/thiourea organocatalyst (Scheme c) .…”
Section: Figurementioning
confidence: 99%